Pengaruh Motivasi Kerja Terhadap Kinerja Perawat Di Puskesmas Wolofeo - Thresia Winarti; Yoseph Darius Purnama Rangga (Jurnal Projemen UNIPA, 2025)
This study entitled "The effect of work motivation and infrastructure on the performance of nurses at Wolofeo Community Health Center. This study aims to determine whether motivation and work infrastructure affect the performance of nurses at the Wolofeo Community Health Center. The population in this study were all nurses who worked at the Wolofeo Health Center, totaling 60 nurses. This study uses a quantitative research approach. The results of statistical tests show that the tcount with a significant value is 0.330. The significance value is greater than the alpha level used 5% (0.05), tcount <ttable 0.982 <2.002, then the decision is to accept the alternative hypothesis (Ha) and reject the null hypothesis (Ho), that partially the motivation variable (X1) is not significant effect on the nurse performance variable (Y).